ASSESSMENT OF THE EFFICACY OF VACCINATION PROGRAMS IN HEALTHCARE WORKERS FOR INFECTION CONTROL - Mana Saeed Mohammed Al Rayshan, Mahdi Mohammed M Alsagour, Hussain Saed Mobark Alhaereth, Hadi Saleh Alhareth, Mahdi Saleh Al-Jumhur, Ali Merzah Alabbas, Mohammad mahdi shilayan Al Balharith, Ali Saeed Al mansour, (Chelonian Research Foundation, 2022)
Introduction: The alarming prevalence of infectious diseases in this population underscores the critical importance of implementing effective preventive measures to mitigate the risks faced by healthcare professionals. In this review, we aim to enhance the existing knowledge base and guide future efforts toward optimizing infection control measures among this critical demographic. Methods: The systematic review rigorously evaluated the efficacy of vaccination programs in healthcare workers for infection control through a meticulous and iterative search strategy, utilizing key terms and targeted databases known for extensive medical literature coverage. ms comprehensive approach aimed to systematically retrieve studies that provided valuable insights into Vaccination program effectiveness, particularly in mitigating infection risks among healthcare workers, a population at heightened exposure to infectious agents. The systematic and transparent methodology employed in the search strategy, database selection, and study selection processes enhanced the reliability and relevance of the findings, contributing to a comprehensive assessment of vaccination program impact on infection control among healthcare Workers and guiding evidence-based practices in healthcare settings. Results: The systematic review synthesized data from nine randomized clinical trials (RCTs) on vaccination programs for infection control among healthcare workers, revealing a broad range Of sample sizes (520 to several thousand participants) and diverse population Characteristics, including various healthcare specialties and settings. The interventions, encompassing Vaccines against influenza, hepatitis B, and measles-mumps-rubella, demonstrated vaccination coverage rates ranging from 72% to 93% , reflecting variations in vaccine types and delivery methods. The overall effectiveness, quantified by a pooled risk ratio of 0.65 (95% CI: 055-0.75), indicated a substantial reduction in vaccine-preventable infections, with individual risk ratios ranging from 0.5 to 0.8. Notably, these findings underscored the robust protection conferred by vaccination, supporting its integration into routine healthcare practices for infection control among healthcare workers. Conclusions: The findings supports the Crucial role of vaccination programs in healthcare workers for infection control, showcasing consistently significant effectiveness across various infectious diseases and emphasizing their vital contribution to safeguarding healthcare professionals and public health. Keywords: Vaccination, Infection Control, Healthcare Workers, Randomized Clinical Trials, Effectiveness